Willingness to use syringe service programs and safe consumption sites among methadone patients with histories of injection drug use in a small Midwest community. (4th May 2022) - Pasman, Emily; Agius, Elizabeth; Victor, Grant; Broman, Michael; Ray, Brad; Resko, Stella
Abstract: Syringe service programs (SSPs) and safe consumption sites (SCSs) are evidence-based strategies to reduce harm associated with injection drug use. However, little is known about the acceptability of these programs outside large urban areas. This study assesses willingness to use SSPs and SCSs among people receiving methadone and with history of injection drug use in a small Midwest community, and identifies factors associated with likely use of each program. Patients recruited from a methadone treatment program completed computer-based surveys (December 2019). Analyses were limited to those reporting histories of injection drug use ( n = 145). Logistic regression was used to identify factors associated with willingness to use each program. Overall, 86.9% indicated likely use of an SSP, and 81.4% indicated likely use of an SCS. Likely SSP users reported more consequences of opioid use. Those without a high school diploma/GED, and those with greater levels of shame were more likely to report willingness to use an SCS. Results indicate SSPs and SCSs are perceived to be useful harm reduction strategies, with increased interest among those who may not be reached by traditional service models. Expansion of these services should be further explored to prevent overdose fatalities and the spread of infectious disease in small communities.